The Effect of Financial Performance on the Health Level of General Insurance Companies - Anastasia Safa Ramadhani; Muazaroh Muazaroh (Almana : Jurnal Manajemen dan Bisnis, 2023)
Insurance is one of the most popular methods of risk transfer. Insurance aims to transfer individual or corporate risk to insurance companies. The purpose of this research is to examine the effect of financial performance on the soundness level of general insurance companies. This research is quantitative research, where quantitative research uses measurement results in the form of numbers and analysis using statistics used to test hypotheses. The population in this study are conventional insurance companies registered with the Financial Services Authority. The sampling technique used purposive sampling. The samples used in this study were 49 samples of conventional general insurance companies. The results showed that the liquidity ratio had a significant positive effect on the soundness level of general insurance companies and the profitability ratio partially had a significant positive effect on the soundness level of general insurance companies. The implication of this research is for insurance companies to stay healthy by maintaining their liquidity and profitability levels.